Mapping the Gravity Center of Fishing Ground on Skipjack Tuna Distribution in Bone Gulf-Flores Sea - Desianty, Sulyana Erma; Zainuddin, Mukti; Safruddin, Safruddin (International Journal of Environment, Agriculture and Biotechnology, 2020)
Bone Gulf and Flores Sea in the Fisheries Management Area 713 (WPP 713) are known as one of the best skipjack tuna fishing areas in Indonesia, where skipjack tuna is an export commodity and has high economic value. The potential of skipjack tuna is based on the spatial-temporal pattern of oceanographic conditions. The distribution of skipjack tuna can be predicted by the biophysical conditions of the environment. Sea surface temperature and chlorophyll-a are biophysical parameters that greatly affect the distribution of skipjack tuna and are often used to predict potential fishing grounds. The study used skipjack fisheries data from April to July in 2017 to 2019 and remote sensing satellite data on sea surface temperature and chlorophyll-a from Aqua / MODIS. This study aims to determine the gravity center of skipjack tuna fishing ground in Bone-Flores Sea using the Generalized Additive Model (GAM). The distribution of skipjack tuna was found to be significantly related (p <0.0001) with preferred range of sea surface temperature at 29.02–31.03 °C and concentration of chlorophyll-a at 0.14–0.44 mg/m3. The gravity center of fishing ground from April shows that skipjack tuna shift to the north in May and June, then back to the south in July. This study dedicated on providing scientific information regarding the gravity center of skipjack tuna fishing ground in Gulf Bone-Flores Sea, as well as the applicability of remote sensing in contributing to optimalization and sustainable utilization of skipjack fisheries resource.